Concurrent blood eosinophils and FeNO as biological therapy indicators in severe asthma: findings from the PRISM study - Pham,DD; Lee,J-H; Kwon,H-S; Song,W-J; Cho,YS; Kim,H; Kwon,J-W; Park,S-Y; Kim,S; Hur,GY; Kim,BK; Nam,Y-H; et al. (The Journal of Allergy and Clinical Immunology: In Practice, 2025)
BackgroundThe combination of pretreatment peripheral blood eosinophil count (BEC) and FeNO levels for optimizing the therapeutic response of T2-biologics in patients with severe eosinophilic asthma (SEA) remains unclear.ObjectiveTo compare longitudinal clinical outcome changes across subgroups stratified by the combination of high and low levels of BEC and FeNO.MethodsOverall, 278 patients with SEA (anti-IL-5/IL-5Rα users: n = 82; and anti-IL-4Rα users: n = 196) were stratified based on pretreatment BEC and FeNO levels and observed for 6 to 12 months. Group differences in exacerbation rate, lung function, Asthma Control Test, BEC, FeNO, and clinical remission over time were compared.ResultsApproximately 75% and 63% of patients presented with concurrent high BEC (≥300 cells/μL) and high FeNO (≥25 ppb) in the anti-IL-5/IL-5Rα and anti-IL-4Rα groups, respectively. Among anti-IL-5/IL-5Rα users, we observed no significant differences among BEC-FeNO groups regarding exacerbation rates or clinical remission. Patients with concurrent high BEC and FeNO levels demonstrated more pronounced reductions in both markers and greater FEV1 and Asthma Control Test score improvements compared with those with high FeNO but low BEC. In the anti-IL-4Rα group, patients with low BEC and FeNO, and those with high BEC but low FeNO, exhibited a significantly lower likelihood of achieving clinical remission (odds ratio [95% CI]: 0.08 [0.00-0.46] and 0.11 [0.01-0.63], respectively) and a slower rate of FEV1 improvement (all P for slope < .05) compared with those with concurrent high BEC and FeNO.ConclusionConcurrently elevated BEC and FeNO levels ensure optimal therapeutic response in patients with SEA who are treated with T2 biologics.Key wordsSevere eosinophilic asthmaBlood eosinophil countFeNOBiologicsAbbreviations usedACTAsthma Control TestBECBlood eosinophil countICSInhaled corticosteroidsNBNegative binomialOCSOral corticosteroidsPRISMPrecisio